The Relationship of Islamic Community Development (PMI) with the Ummah of Medina - Saputra, Acep; Syukur, Abdul (EDUCATIO : Journal of Education, 2023)
This research focuses on the analysis of the relationship between efforts to empower the Islamic community (PMI) and the concept of the Ummah of Medina in the context of Islamic history. This study employs a historical approach and literature analysis to investigate how the concept of the Ummah of Medina has influenced the empowerment efforts of PMI throughout Islamic history and how this relationship has evolved over time. The results of the research indicate that in the context of the Charter of Medina, the concept of the ummah plays a central role as the foundation for cooperation and agreements among various groups and communities in Medina at that time. The Charter emphasizes that the believers and Muslims are one united ummah, regardless of their ethnicity or background. This reflects the principles of unity and solidarity in Islam.